The Cambridge Handbook of Sociolinguistics - Mesthrie, Rajend (Cambridge : Cambridge University Press, 2011)
The most comprehensive overview available, this Handbook is an essential guide to sociolinguistics today. Reflecting the breadth of research in the field, it surveys a range of topics and approaches in the study of language variation and use in society. As well as linguistic perspectives, the handbook includes insights from anthropology, social psychology, the study of discourse and power, conversation analysis, theories of style and styling, language contact and applied sociolinguistics. Language practices seem to have reached new levels since the communications revolution of the late twentieth century. At the same time face-to-face communication is still the main force of language identity, even if social and peer networks of the traditional face-to-face nature are facing stiff competition of the Facebook-to-Facebook sort. The most authoritative guide to the state of the field, this handbook shows that sociolinguistics provides us with the best tools for understanding our unfolding evolution as social beings.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Sociolinguistics